Education and psychological distress in adolescence and mid‐life: Do private schools make a difference?. (26th August 2020) - Sullivan, Alice; Parsons, Samantha; Ploubidis, George; Wiggins, Richard D.; Green, Francis
Abstract : This article extends the evidence base on childhood circumstances, education and psychological distress. We examine the link between childhood advantage and disadvantage, the type of school attended during adolescence and psychological distress at ages 16 and 42. The analysis uses a large, population‐based birth cohort study, the 1970 British Cohort Study (BCS70) ( n = 17, 198) using a structural equation modelling (SEM) approach. More advantaged young people were more likely to attend private schools, but we find no evidence for an effect of private schooling on psychological distress for men, and for women there was an association between private schooling and raised psychological distress at age 16. Having a university degree was associated with a modest reduction in psychological distress in mid‐life. We establish that maternal psychological distress at age 10 was a risk factor for the offspring's psychological distress both in adolescence and in mid‐life, and adolescent psychological distress predicts psychological distress in mid‐life. We conclude that schools which are academically successful do not necessarily provide wider benefits in terms of mental health.